Vaccination Against COVID-19 Disease During Pregnancy - Voiniušytė, Austėja; Černiauskaitė, Miglė; Paliulytė, Virginija; Einikytė, Rūta; Ramašauskaitė, Diana (Acta medica Lituanica, 2022)
Background. The effect of COVID-19 disease during pregnancy is still under investigation, however scientific studies have shown that pregnant women with COVID-19 infection are at increased risk for severe illness or complications [1]. Risk factors for severe disease and death in pregnancy include maternal age (especially ≥35 years), obesity, preexisting medical comorbidities (particularly hypertension and diabetes or more than one comorbidity), and being unvaccinated [2]. Many societies of obstetricians and gynecologists recommend that all pregnant patients undergo COVID-19 vaccination [1]. The aim of this study is to observe demographic characteristics, including education, place of residence and type of employment of women who chose to be vaccinated against COVID-19 in Lithuania, as well as to investigate any adverse reactions following the COVID-19 vaccine during pregnancy and compare the results to published scientific data. Materials and methods. An online questionnaire for pregnant women primarily located in Lithuania who received at least one dose of COVID-19 vaccine before giving birth has been launched in July, 2021. Data were entered via Google Forms and analyzed using Microsoft Excel and IBM SPSS Statistics. Literature review was performed on PubMed and Google Scholar search engines on inclusion criteria: publication date 2019–2021, used keywords pregnancy, COVID-19, vaccination, side effects. Results. Data were collected from 227 women vaccinated against COVID-19 during pregnancy. It was observed that the most chosen vaccine was Pfizer-BioNTech BNT162b2 (196 out of 227 individuals (86%)). More pregnant women confirmed having fever after the second dose compared to the first dose (p=0.006). In addition, injection site pain was the most common local side effect after both doses (98%) and more common after the first dose compared to the second (p=0.002). Regarding systemic reactogenicity more women experienced fatigue after the second dose comparing to the first dose (p=0.01). Furthermore, more women were unable to engage in daily activities after the second dose (p=0.03). All other symptoms did not differ after doses 1 and 2. Conclusions. Overall findings of this study did not suggest any obvious safety signals among pregnant individuals who received COVID-19 vaccine and all the side effects were comparable to the general population. Completed literature review indicates that pregnant women vaccinated against COVID-19 experience the same side effects as individuals in general population and no specific postvaccination reactions among pregnant individuals are observed.